Model Pengelolaan Kawasan Teknopolitan - Warseno Warseno (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Teknopolitan area concept is the result of collective consensus and harmony among the various parties that can create a clear advantage, especially those who become the central role in the teknopolitan region, namely government, universities/research institutes, and industry. The government of Pelalawan initiated build teknopolitan region based on the potential of abundant natural resources, especially oil palm plantations. To encourage the establishment of such areas needs to be supported teknopolitan managers adequate institutional aspects. The purpose of this study was to develop a model teknopolitan area management within the framework of the Regional Innovation System (SID). To realize these goals, the objectives to be achieved are (1) completion of the concept teknopolitan in Pelalawan region. (2) determined the institutional model complement the concept of regional development, especially in Pelalawan teknopolitan.Keywords: Concept of Regional Development, Pelalawan Teknopolitan